INNOVATIVE METHODS IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Islomova Aziza Hasan qizi; Bobonazarov Abror Nodir o’g’li (Ta’lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT This study examines innovative approaches to teaching English as a foreign language, with a focus on contemporary strategies that strengthen learners’ motivation, interaction, and language skills. It reviews the use of digital technologies, communicative methods, project-based learning, and gamification as powerful tools for enhancing teaching effectiveness. The article underlines the benefits of incorporating multimedia resources, cooperative tasks, and learner-centered practices to make English instruction more engaging and productive. Particular emphasis is placed on the teacher’s role in adjusting methods to various educational contexts and students’ needs. The research concludes that innovation in language education supports creativity, critical thinking, and long-term mastery of the language.